2021
DOI: 10.1155/2021/9935410
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA SNHG3 Promotes Gastric Cancer Cells Proliferation, Migration, and Invasion by Targeting miR-326

Abstract: The function and possible mechanism of lncRNA Small Nucleolar RNA Host Gene 3 (SNHG3) in GC have not been fully studied. The aim of our study was to investigate the role of SNHG3 in the proliferation, migration, and invasion of GC cell lines. The expressions of SNHG3, miR-326, and TWIST in GC9811-P GC cell lines were detected by RT-qPCR. Western blotting was performed to detect the protein levels of TWIST and EMT-related genes. Luciferase reporter gene analysis and RNA immunoprecipitation (RIP) analysis confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…miR-222-3p can inhibit formation of medulloblastoma stem-like cells by targeting Notch2/c-myc signaling pathway, and it can suppress cell viability, alter cell cycle distribution, and inhibit the formation of MB stem-like cells via the Notch2/c-myc pathway [50] . Relevant lncRNA, SNHG3, may promote gastric cancer progression through the miR-326/TWIST axis and provide a new diagnostic and prognostic biomarker [51] . Indeed, all the 3 RNAs have been validated cross-talks with other RNAs as discussed above, and interactions of diverse RNAs have been widely concerned especially that lncRNA can perturb target mRNA expression via interacting miRNA as a competing endogenous RNA.…”
Section: Discussionmentioning
confidence: 99%
“…miR-222-3p can inhibit formation of medulloblastoma stem-like cells by targeting Notch2/c-myc signaling pathway, and it can suppress cell viability, alter cell cycle distribution, and inhibit the formation of MB stem-like cells via the Notch2/c-myc pathway [50] . Relevant lncRNA, SNHG3, may promote gastric cancer progression through the miR-326/TWIST axis and provide a new diagnostic and prognostic biomarker [51] . Indeed, all the 3 RNAs have been validated cross-talks with other RNAs as discussed above, and interactions of diverse RNAs have been widely concerned especially that lncRNA can perturb target mRNA expression via interacting miRNA as a competing endogenous RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have elucidated the high expression of SNHG3 in acute myeloid leukemia (AML)[ 74 ], esophageal cancer[ 75 ], gastric cancer (GC)[ 76 - 78 ], laryngeal carcinoma[ 79 , 80 ], oral squamous cell carcinoma[ 81 , 82 ], osteosarcoma[ 83 , 84 ], and prostate cancer[ 85 , 86 ], but have not yet explored the relationship between SNHG3 and clinicopathological features. Subsequent investigations into the biological mechanisms of SNHG3 in other diseases will further support the potential of SNHG3 as a new diagnostic and therapeutic biomarker.…”
Section: Clinical Characters Of Lncrna Snhg3mentioning
confidence: 99%
“…These lncRNAs are called ceRNAs. Numerous studies have found that SNHG3 can function as a ceRNA by competitively binding to various miRNAs, including miR-758-3p[ 74 ], miR-515-5p[ 87 ], miR-330[ 29 ], miR-326[ 25 , 30 , 34 , 78 ], miR-384[ 31 , 39 , 79 ], miR-154-3p[ 32 ], miR-186-5p[ 33 , 75 ], miR3173–5p[ 89 ], miR-139-5p[ 35 ], miR-539[ 36 ], miR-182-5p[ 37 ], miR-370-5p[ 38 ], miR-3619-5p[ 76 ], miR-485-5p[ 40 ], miR-128[ 41 ], miR-214-3p[ 42 , 52 ], miR-340-5p[ 45 , 80 ], miR-890[ 68 ], miR-1343-3p[ 43 ], miR-216a[ 46 ], miR-515-5p[ 47 ], miR-2682-5p[ 81 ], miRNA-151a-3p[ 83 ], miR-196a-5p[ 84 ], miR-339-5p[ 49 ], miR-139-5p[ 51 ], miR-577[ 85 ], and miR-487a-3p[ 86 ]. In HCC SNHG3 plays its role as a ceRNA mainly by binding to miR-128[ 41 ], miR-326[ 25 ] and miR-214-3p[ 42 ].…”
Section: Biological Function Of Snhg3 In Cancermentioning
confidence: 99%
“…Depletion of SNHG3 significantly inhibits the proliferation, migration, and invasion of GC cell lines. SNHG3 acts as an endogenous sponge to reduce the expression of miR-326 and regulates the expression of TWIST by competitively binding to miR-326 ( Rao et al, 2021 ). Overexpression of small nucleolar RNA host gene 7 (SNHG7) has been reported in most human tumors, including lung cancer, and it acts as an oncogenic lncRNA in GC and may be a promising therapeutic candidate for GC patients.…”
Section: Lncrnas Regulate Emt-induced Metastasis In Gc Through Spongi...mentioning
confidence: 99%